Proč moje děti nechodí do mateřské školy. Přístup rodičů, jejichž rozhodování neomezuje socioekonomické znevýhodnění - Helena Picková (Karolinum Press, 2018)
The study presented here aims to understand why some parents from ordinary middle-class families do not send their preschool children to kindergarten or send them only very irregularly. Data from indepth interviews with mothers, which was obtained as part of the longitudinal monitoring of six families from the Liberec region during the pre-school year and commencement of compulsory education, was subjected to a content analysis. The analysis identified four main themes: a strong protective family style of education; compensating for problems experienced during the parents' own childhood; mistrust that the kindergarten will ensure the child's comprehensive development, and early scholarization. The results are discussed with regard to the enactment of compulsory attendance of the pre-school year of kindergarten.